2016
DOI: 10.1596/1813-9450-7578
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Activity and Money Laundering from an Economic Growth Perspective: A Model and an Application to Colombia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Influence of money laundering has on economic development [23] mentioned that Money laundry is one of those international phenomena which have affected the whole world and even after so many precautions and implementation of rules and regulations, it is still happening on a very large ratio. It is a fact that this issue has affected the economy of the world very drastically especially the economy of those countries which are actually being used by money launders.…”
Section: -Effect Of the Entry Of Money Laundering On The Currency Anmentioning
confidence: 99%
“…Influence of money laundering has on economic development [23] mentioned that Money laundry is one of those international phenomena which have affected the whole world and even after so many precautions and implementation of rules and regulations, it is still happening on a very large ratio. It is a fact that this issue has affected the economy of the world very drastically especially the economy of those countries which are actually being used by money launders.…”
Section: -Effect Of the Entry Of Money Laundering On The Currency Anmentioning
confidence: 99%
“…In our globalization times tax collection evolved in an impossible mission due to offshore banking, invoices and investments triangles and unlimited tax avoidance tricks on the edge of legality. We study for years' money laundering antisocial policies like Bank capture, Black salaries, Bulk cash smuggling, Cash-intensive businesses, Casinos, Fictional loans, Real estate, Round-tripping, Shell companies and trusts, Structuring, Trade-based laundering etc [14,18]. However, these and a lot more represent the dark side of the tax collection system.…”
Section: Introductionmentioning
confidence: 99%
“…Such figures increase over time but unlike crime rates, never appear to fall (see, for example, [14]), only 10 The World Bank is attempting to develop more sophisticated models for the estimation of money laundering at the national level. For an early effort with Colombia see Villa et al [15]. 11 Michel Camdessus, then the Managing Director of the IMF, did not claim that the IMF had produced the estimate but only that such estimates had been made by others: however this refinement has been lost in the subsequent narratives.…”
mentioning
confidence: 99%
“…14 A RAND study suggested that 2005 Mexican Drug Trafficking Organizations' gross revenues (significantly more than their net profits) from moving drugs into the United States total $5.1 billion ( [27], p. 30), plus relatively modest further income in the low hundreds of millions from people trafficking. 15 Even taken at face value, however, these numbers are only weakly related to money laundering. Fearsome though they may be, Mexican DTOs have large expenses in bribes to law enforcement and politicians (which may have to be laundered only when they are above a rather high threshold of lifestyle and patronage expenditures); and they have large levels of 'staffing' to support, mainly in cash from cash proceeds of crimes.…”
mentioning
confidence: 99%
See 1 more Smart Citation